2001
DOI: 10.1097/00007632-200109010-00025
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Resection and Reconstruction for Primary Osteogenic Sarcoma of the Second Cervical Vertebra

Abstract: The axis is a very rare location for the occurrence of primary osteosarcoma. Osteosarcoma may histologically mimic chondroblastoma. The axis can be surgically exposed, resected, and instrumented transorally. The stabilization must be augmented by posterior occipitocervical fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…Goel et al [10] reported a patient with congenital basilar invagination after odontoidectomy performed with plate and screw fixation of the clivus to the body of the 3rd cervical vertebra. It was considered that direct fixation to the clivus may be a more rigid alternative to previously described techniques [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Goel et al [10] reported a patient with congenital basilar invagination after odontoidectomy performed with plate and screw fixation of the clivus to the body of the 3rd cervical vertebra. It was considered that direct fixation to the clivus may be a more rigid alternative to previously described techniques [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that direct fixation to the clivus is more practical and robust than techniques previously described for the reconstruction after ventral resection of the lesions and decompressions in the CVJ [6,10,11]. Since a novel anterior fixation using the clivus as the sole cephalad anchoring point was applied to one patient with congenital basilar invagination after odontoidectomy [3], a modified Harms mesh and a custom titanium plate technique anchoring at the clivus and C3 were used for the treatment following extensive resection of the upper cervical spine [2,4].…”
Section: Discussionmentioning
confidence: 99%
“…2 Ozaki et al and the Cooperative Osteosarcoma Study Group have reported better overall survival when wide marginal excision is achieved (compared with intralesional debulking). 3 The limitations of radiotherapy, due to the harmful effects on the spinal cord, can be reduced with advanced techniques. To minimize harm, IMRT and proton radiation therapy allow accurate radiation doses to be delivered effectively to the residual tumour.…”
Section: Discussionmentioning
confidence: 99%
“…The interval between the ''normal'' radiograph and the second, which showed complete destruction of the C3 body, was only three months. The histology, 8 1 + + + DOD (24) 1979 9 1 + + + DOD (24) NED 1984 10 1 + + + NED (7) 1986 11,à 3 +(2/3) +(3/3) +(1/3) DOD (7-11) 1988 12 1 + + + AWD (24) 1988 13 2 + + À DOD (36) and NED (12) 1988 14 1 + + + DOD (12) 1991 15 1 + + À DOD (7) 1994 16 1 + À + NED (24) 1996 17 1 + + + DOD (24) 2002 4, 1/22 + + + AWD (26) 2001 3 1 + + + AWD (40) 2002 6 1 + À + NED (10) 2004 18 1 + À + DOD (10) 2005 19 1 + + + DOD (2) 2006 20 1 together with the rapid re-growth of the tumour after the first surgery, confirmed the aggressiveness of the tumour. Therefore, a high index of suspicion is required for the diagnosis of cervical spinal osteosarcoma, despite its rarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation